Enhanced thermoelectric performance of CuGaTe2 by Gd-doping and Te incorporation. (May 2015) - Zhang, Jian; Qin, Xiaoying; Li, Di; Song, Chunjun; Zhu, Xiaoguang; Liu, Yongfei; Xin, Hongxing; Chen, Li; Zou, Tianhua
Abstract: Gd-doped compounds CuGa1−x Gdx Te2 (0 ≤ x ≤ 0.02) incorporated with tellurium nanoparticles are synthesized by fusion method. Their thermoelectric properties are investigated in the temperature range of 300–800 K. The results indicate that the synergistic effect of Gd-doping and Te incorporation remarkably enhances the thermoelectric performance of CuGaTe2 . Specially, the thermal conductivity κ of the specimen CuGa0.98 Gd0.02 Te2 /0.7 vol.%Te reduces to 0.45 Wm −1  K −1 at 684 K, which is ∼74% smaller than that of pure CuGaTe2 (κ = 1.76 W m −1  K −1 at 684 K) due to the incorporation of nanostructure Te. The thermoelectric figure of merit value (ZT) reaches 0.75 at 737 K for the specimen CuGa0.99 Gd0.01 Te2 /0.7 vol.%Te, which is ∼115% larger than that of pure CuGaTe2 . Highlights: The effect of Gd-doping and Te incorporation on the thermoelectric performance of CuGaTe2 is studied. The thermal conductivity κ is reduced by Gd-doping and Te incorporation. The maximum ZT = 0.75 at 737 K is obtained for the specimen CuGa0.99 Gd0.01 Te2 /0.7 vol.%Te.